Michael addition of dehydroalanine‐containing MAPK peptides to catalytic lysine inhibits the activity of phosphothreonine lyase. Issue 23 (28th October 2015) - Zhang, Yuan; Yang, Ru; Huang, Juan; Liang, Qiujin; Guo, Yanmin; Bian, Weixiang; Luo, Lingfei; Li, Hongtao
Abstract : The phosphothreonine lyases OspF and SpvC irreversibly inactivate host dual‐phosphorylated mitogen‐activated protein kinases (MAPKs) [pThr‐X‐pTyr motif] through β‐elimination. We found that dual‐phosphorylated (pSer‐X‐pTyr) MAPK substrate peptides and their resulting catalytic products cross‐link to OspF and SpvC. Mass spectrometry results revealed that these linkages form between lysine, which acts as a general base, and dehydroalanine (Dha) on catalytic products. The nucleophilic addition efficiency is dependent on the K136 residue being in a deprotonated state. Peptide cross‐linking inhibits the activity of SpvC and blocks the inactivation of MAPK signaling by SpvC. Small compounds mimicking these sequences may act as phosphothreonine lyase inhibitors. Abstract : Dehydroalanine‐containing MAPK peptides can be cross‐linked to phosphothreonine lyase. MAPK peptide linkage occurs through the catalytic lysine on phosphothreonine lyase. MAPK peptide adduct formation inhibits phosphothreonine lyase activity and blocks its inactivation of MAPK signaling.